Scour below a non-full flowing rectangular culvert outlet - Tan, Bei'er. (2013)
In this study of scour below a non-full flowing rectangular culvert outlet, experiments were conducted to investigate, understand and predict scour hole formation and its geometry. Five sets of experiments with uniform sediment bed particles of median size, d50 1.63 mm and standard deviation, σg of 1.19 but varying tailwater depth levels and flow rates were conducted for 48 hours so that the scour hole formation to reach its equilibrium stage.